KAJIAN SISTEM PENGELOLAAN SAMPAH DI KOTA PALANGKA RAYA DAN PENGARUHNYA TERHADAP KUALITAS AIR LINDI - Yessica, Nadya; Biyatmoko, Danang; Akbar, Arief R. M.; Indrayatie, Eko Rini (EnviroScienteae, 2023)
Waste management in Palangka Raya City is in the Km Landfill. 14. The landfill is divided into 2 activities, namely waste management and leachate management installation. The waste management system is a method applied at the end point of waste processing. Waste collected at the landfill arrives at the landfill. The purpose of this study is to analyze waste generation, waste composition, and waste sources, analyze whether the waste management method affects the quality of leachate water and groundwater of the surrounding residents, and analyze the pollution index in the groundwater of the surrounding residents. This study uses a quantitative descriptive method by analyzing leachate and groundwater samples examined at the regional health laboratory. The results of these samples will be compared with leachate water quality standards, groundwater quality standards for sanitary hygiene purposes, and groundwater pollution index tests. The quality of leachate is unaffected by the operational method of waste processing. All leachate water samples for the parameters TSS and Cadmium are below the quality standard for final waste processing, except for the TSS value at station St2, this is because the wastewater is still in the waste pile area and has not yet entered the leachate management installation pond. The results of groundwater sample tests in several residents' homes for the pH parameter are below the quality standard. The pollution index results show that the water used daily is categorized as lightly polluted.